The role of Chloroquine phosphate on rheumatoid factor in patients with knee osteoarthritis - Saleh, Eman S.; Turki, Kismat M.; Alosami, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Osteoarthritis (OA) is disorder of diarthrodial joints characterized clinically by pain and functional limitation. Rheumatoid factor (RF) represents one of routine laboratory tests that done for all patients have joint complaints. Chloroquine phosphate (CQP) is a disease modifying antirheumatic drug (DMARD) used for patients suffer from knee osteoarthritis (KOA) in order to reduce their RF value and improves the disease status.Objective: To evaluate the effect of chloroquine phosphate on rheumatoid factor (RF) level in serum of patients with knee osteoarthritis KOA) Design: case report.Subjects and methods: RF value were assessed quantitatively by ELISA technique before and after treatmtnt for a total of fifty five patients with KOA (30 femal and 25 male) their age ranged from (50-66 years) selected randomly from out patient clinic in Baghdad Teaching Hospital , Medical City Baghdad; suffering from KOA. All patients were treated with oral dosage form of CQP for one month twice daily. Results: Mean serum RF level was significantly reduced (p